2012
DOI: 10.1007/s00128-012-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Atrazine, S-Metolachlor, and Permethrin to Typha latifolia (Linneaus) Germination and Seedling Growth

Abstract: Phytotoxicity assessments were performed to compare responses of Typha latifolia (L.) seeds to atrazine (only) and atrazine + S-metolachlor exposure concentrations of 0.03, 0.3, 3, and 30 mg L(-1), as well as permethrin exposure concentrations of 0.008, 0.08, 0.8, and 8 mg L(-1). All atrazine + S-metolachlor exposures resulted in significantly reduced radicle development (p < 0.001). A stimulatory effect for coleoptile development was noted in the three highest atrazine (only) exposures (p = 0.0030, 0.0181, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…Recently, phytotoxicity of atrazine to a certain emergent macrophyte was evaluated using different endpoints. The development of radicles in seeds of Typha latifolia exposed to 30 mg L −1 atrazine was significantly less than radicles in controls, though no significant differences were found in germination between the control and this concentration (Moore and Locke 2012). With respect to plant growth, exposures to low environmentally relevant concentrations have generally failed to detect any effect, whereas higher concentrations of atrazine have been shown to decrease the biomass of emergent plants (EC 50 =5.24 mg L −1 for T. angustifolia, 8.76 mg L −1 for T. latifolia) (Marecik et al 2012).…”
Section: Introductioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Recently, phytotoxicity of atrazine to a certain emergent macrophyte was evaluated using different endpoints. The development of radicles in seeds of Typha latifolia exposed to 30 mg L −1 atrazine was significantly less than radicles in controls, though no significant differences were found in germination between the control and this concentration (Moore and Locke 2012). With respect to plant growth, exposures to low environmentally relevant concentrations have generally failed to detect any effect, whereas higher concentrations of atrazine have been shown to decrease the biomass of emergent plants (EC 50 =5.24 mg L −1 for T. angustifolia, 8.76 mg L −1 for T. latifolia) (Marecik et al 2012).…”
Section: Introductioncontrasting
confidence: 49%
“…1) can partially alleviate negative effects on plant growth. Additionally, low atrazine concentrations resulted in a stimulatory effect on stimulate plant shoot length, leaf blade, and stem diameter (Esser et al 1975;Moore and Locke 2012). To some extent, it was conducive to recovery of plant growth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lytle and Lytle [43] showed J. effusus growth to be significantly inhibited by atrazine concentrations as low as 96 μg L −1 , specifically new shoot development. Similarly, Moore and Locke [44] observed that mixtures of atrazine and S-metolachlor significantly reduce radicle development in Typha latifolia seedlings at concentrations as low as 31 μg L −1 of the mixture, noting that S-metolachlor is a long-chain fatty acid inhibitor. [44] If plant growth and possibly plant metabolism slow in the presence of both atrazine and S-metolachlor, N metabolism will also be inhibited and concomitantly reduce N uptake rates.…”
Section: Wetland Nutrientsmentioning
confidence: 94%
“…Similarly, Moore and Locke [44] observed that mixtures of atrazine and S-metolachlor significantly reduce radicle development in Typha latifolia seedlings at concentrations as low as 31 μg L −1 of the mixture, noting that S-metolachlor is a long-chain fatty acid inhibitor. [44] If plant growth and possibly plant metabolism slow in the presence of both atrazine and S-metolachlor, N metabolism will also be inhibited and concomitantly reduce N uptake rates. This would, in turn, affect the rate at which N dissipates from the water column and increase agricultural run-off storage time needed for a wetland to process and remove N before exiting into a river or stream.…”
Section: Wetland Nutrientsmentioning
confidence: 94%